Cryptocurrency Disclosure and valuation in the financial Report in Delhi City - Shivam Patel; Abhishek Ratnani; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2025)
This research investigates the perceptions and awareness of cryptocurrency disclosure and valuation, with a particular focus on gender differences among respondents in India. As digital currencies gain prominence in global financial markets, understanding the level of awareness, regulatory clarity, and organisational readiness for cryptocurrency disclosure becomes critical for transparency and investor confidence. A total of 154 respondents participated in this study, comprising students, early-career professionals, and business professionals. The study employed a structured questionnaire covering key aspects such as organisational awareness, regulatory clarity, management discretion, valuation methods, price volatility, blockchain integration, and investor confidence. Reliability of the measurement scale was confirmed through Cronbach’s Alpha (0.829), indicating high internal consistency. Frequency analysis revealed that younger individuals (18–35 years) are more engaged with cryptocurrencies, while a majority of respondents demonstrated neutral to moderate awareness regarding disclosure and valuation practices. Chi-square tests were conducted to examine the association between gender and perceptions of cryptocurrency-related issues. Significant gender-based differences were observed in awareness of disclosure requirements, clarity on valuation methods, and perceived challenges due to price volatility.